Effectiveness of the school executive development program - Rusgal, Milandre Bugarin 1939-
Stepwise multiple regression analysis was used to treat and analyze the self perceptions and post training managerial capabilities of 385 superintendents, assistant superintendents and supervisors from 126 school divisions who had undergone training in the School Executive Development Program, a joint undertaking of the Miistry of Education, Culture and Sports and the Civil Service Commission. The program is positively related to management knowledge, managerial behavior (skills) and managerial capabilities but not to managerial attitudes. Organization structures appeared to be the most important determinant of managerial attitudes.